2020
DOI: 10.5114/pjp.2020.97017
|View full text |Cite
|
Sign up to set email alerts
|

Are there EWSR1 rearranged cutaneous hidradenomas and mucoepidermoid carcinomas of salivary glands? A FISH study and review of the literature

Abstract: MAML2 rearrangements have been previously described for hidradenomas and mucoepidermoid carcinomas (MEC). However, one report showed EWSR1 rearrangement in both tumours. In this study, EWSR1 and MAML2 translocation were investigated in hidradenomas and MECs. Specimens from thirteen MECs of the salivary glands and twenty hidradenomas of the skin were evaluated. Fluorescence in situ hybridisation (FISH) studies with EWSR1 and MAML2 break-apart probes were used. Forty percent of hidradenomas and 84.6% of MECs sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The rate of MAML2 translocation in hidradenomas has believed thought to be in the 50% range. 5,[15][16][17] The significant Winnes et al 6 Krypchova et al 15 Kuma et al 16 Bozdogan et al 17 Sekine et al 19 Behboudi et al 13 Seethala et al 14 Roden et al 24 Bean et al 25 Antonescu et al 30 Vivero et al 31 Zhao et al 32 BAP, break-apart probe; RT-PCR, reverse-transcription polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of MAML2 translocation in hidradenomas has believed thought to be in the 50% range. 5,[15][16][17] The significant Winnes et al 6 Krypchova et al 15 Kuma et al 16 Bozdogan et al 17 Sekine et al 19 Behboudi et al 13 Seethala et al 14 Roden et al 24 Bean et al 25 Antonescu et al 30 Vivero et al 31 Zhao et al 32 BAP, break-apart probe; RT-PCR, reverse-transcription polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of MAML2 translocation in hidradenomas has believed thought to be in the 50% range. 5,15–17 The significant fraction of apparently translocation-negative hidradenomas raised the question of whether there might exist alternate pathways of molecular pathogenesis in hidradenomas. Indeed, we initially intended to identify and then further characterize MAML2 -negative hidradenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discordant or controversial data: EWSR1::POU5F1 fusion has been described in tumors diagnosed as hidradenoma in a single report [58] but has not been further confirmed [59]. A subsequent study has shown that this fusion defined a subset of myoepithelial tumors that can be mistaken for hidradenoma due to an extensive clear cell morphology [60] (cf.…”
Section: Hidradenomamentioning
confidence: 99%
“…Discordant or controversial data: EWSR1::POU5F1 translocation is frequent in a subset of myoepithelial tumors with frequent extensive clear cell morphology that can be mistaken for hidradenoma [60]. In this context and before the description of this fusion in clear cell myoepithelial neoplasms, EWSR1::POU5F1 had been reported in tumors diagnosed as hidradenoma in a single report [58] but was not confirmed afterwards [59] (cf. : hidradenoma).…”
Section: Myoepitheliomamentioning
confidence: 99%